(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2020)
Background: Job enrichment is an idea developed by Frederick Herzberg. It is a job design technique of motivating employees by adding responsibility and variety to their job. It is a vertical expansion of the job with the aim to make the position more satisfying and add value to the employee’s job. Job Enrichment when applied in hotels can help adding value to employees’ jobs, cope dissatisfaction, attrition and retaining employees in the organization. Objective: The present study extended to study the role of job enrichment in motivating and retaining the hotel employees. Methodology: A structured questionnaire was adopted & the study was conducted in a hotel of Delhi. Convenience sampling technique was used and the sample size consisted of 30 hotel employees. Results: The findings of the study showed that employees believed that job enrichment has a significant effect in increasing motivation (76%), decreasing absenteeism (55%) and reducing turnover (43%) in hotels. Conclusion: Human Resources department in hotels should consider implementing various approaches of job enrichment which includes giving task variety, increasing autonomy, feedback on regular basis in order to deal with dissatisfaction and turnover of employees.